Reasons to remember security cooperation and the politics of memory in Japan and South Korea - Chan, Aloysius Zhekang (Nanyang Technological University, 2022)
The dearth of security cooperation between Japan and the Republic of Korea has often been explained with reference to ideation (the troubled history between the two states) or material factors (divergent priorities and practical disputes). Judging those accounts to be insightful but incomplete, this dissertation examines Japan and South Korea’s reasons to remember and retain their antipathy. Working from social constructivist precepts and scrutinising the ‘politics of memory,’ I argue that Japan- ROK relations can be better understood with attention to mechanisms that both harness and contribute to the intensity and political salience of memory. First, state leaders have exploited the power of history and dynamics of otherisation to domestic political ends; in so doing, they reproduce and reify memory. Second, bilateral disputes and competitions rooted in conceptions of history serve to affirm and accentuate memories of uneven power dynamics. Third, regional structures and interactions have preserved the wedge of history from without. I suggest that this approach not only sheds light on the specific subject of Japan-ROK relations, but can also aid the general study of tension and reconciliation between historically opposed states.